2023
DOI: 10.3390/cancers15235596
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gene Fusions in Thymic Epithelial Tumors

Anja C. Roden

Abstract: Thymic epithelial tumors (TET) are rare and large molecular studies are therefore difficult to perform. However, institutional case series and rare multi-institutional studies have identified a number of interesting molecular aberrations in TET, including gene fusions in a subset of these tumors. These gene fusions can aid in the diagnosis, shed light on the pathogenesis of a subset of tumors, and potentially may provide patients with the opportunity to undergo targeted therapy or participation in clinical tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…A number of recurrent molecular aberrations in TET have already been identified, making molecular studies for TET a diagnostically important tool. Intriguingly, most of the recurrent gene fusions in TET involve mastermind-like transcriptional coactivator 2 (MAML2) gene, namely, MAML2::CRTC1 in mucoepidermoid carcinoma, MAML2::KMT2A in a subset of B2 and B3 thymomas, and importantly regarding the current case, YAP1::MAML2 in metaplastic thymoma [4]. Zhao et al in their study of 17 metaplastic thymoma cases proved that YAP1::MAML2 rearrangement is found in both epithelioid and spindle cell components, which again confirms the neoplastic origin of the spindle cell/stroma-like component [6].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…A number of recurrent molecular aberrations in TET have already been identified, making molecular studies for TET a diagnostically important tool. Intriguingly, most of the recurrent gene fusions in TET involve mastermind-like transcriptional coactivator 2 (MAML2) gene, namely, MAML2::CRTC1 in mucoepidermoid carcinoma, MAML2::KMT2A in a subset of B2 and B3 thymomas, and importantly regarding the current case, YAP1::MAML2 in metaplastic thymoma [4]. Zhao et al in their study of 17 metaplastic thymoma cases proved that YAP1::MAML2 rearrangement is found in both epithelioid and spindle cell components, which again confirms the neoplastic origin of the spindle cell/stroma-like component [6].…”
Section: Discussionmentioning
confidence: 80%
“…The major hint leading to the correct diagnosis should be the unusual "stroma" with dense fibroblast-like cells, regardless of its proportion in the tumor. Another histological difference between the two types is the scattered thymocytes in type A thymoma which is typically lacking in the metaplastic type [4]. An unusual immunomarker expression in the stroma-like component, such as EMA, keratin, and Islet-1 could also be helpful.…”
Section: Discussionmentioning
confidence: 99%